Metabolic consequences of overlapping food restriction and cell-mediated immune response in a long-distance migratory shorebird, the little ringed plover Charadrius dubius - Sánchez Gutiérrez, Jorge; Masero Osorio, José Antonio; Abad Gómez-Pantoja, José María; Villegas Sánchez, María Auxiliadora; Sánchez Guzmán, Juan Manuel (Journal of Avian Biology, 2011)
Investment in immunity is commonly viewed as an energetically costly activity in birds. Although several studies have focused on the energy cost of mounting an immune response and its concomitant physiological trade-offs, nothing is known about the metabolic adjustments experienced by immunochallenged birds under resource limitation, or about the basal metabolism cost of mounting cell-mediated immune (CMI) responses in bird species other than non-migratory passerines. Here we measured the basal metabolic rate (BMR), inflammatory response, and body mass in ad libitum fed and food-restricted little ringed plovers Charadrius dubius challenged with phytohemagglutinin (PHA) in order to assess the energy cost, the strength, and the time course of the CMI response in a long-distance migratory bird in different nutritional states. We found that ad libitum birds injected with PHA significantly increased both mass-independent BMR and inflammatory response, whereas birds with an induced food restriction-immune response overlap experienced a mass-independent BMR downregulation and decreased inflammatory response relative to ad libitum birds. We suggest that both the BMR downregulation and the diminished inflammatory response observed in birds facing such an overlap could be energy-saving mechanisms to maintain the body mass above a critical level and maximize fitness. We thank Andreas Mölich for providing helpful advice on metabolic measurements. Financial support was provided by the project CGL2006-01227 of the Spanish Ministry of Science and Innovation. This study is part of a PhD fellowship from Junta de Extremadura to JSG. The manuscript benefited from the comments of Wolfgang Goymann and two anonymous referees on an earlier version. peerReviewed